A New Method for the Benzylic Oxidation of Alkylarenes Catalyzed by Hypervalent Iodine(III) - Xu, Yuan; Yang, Zhenping; Hu, Jiantao; Yan, Jie (Synthesis, 2013)
A convenient and simple procedure is described for the oxidation of the benzylic C–H moiety of alkylarenes to give the corresponding aryl ketones, using tert-butyl hydroperoxide and m-chloroperoxybenzoic acid in the presence of a catalytic amount of the hypervalent iodine reagent, (diacetoxyiodo)benzene. The reactions typically occur in good yields in 2,2,2-trifluoroethanol as the solvent and at room temperature.
Keywords: benzylic oxidations; hypervalent iodine reagent; (diacetoxyiodo)benzene; ketones